Risk Analysis of Domino Effect Due to Fire in Petroleum Plants - Me’eraj, Abdul Rasyid (IRC, 2020)

(untitled)
Fire accidents in petroleum plants are one of the common issues that happen in the industry nowadays. The facilities and equipment in petroleum plants have the risks to involve in accidents specifically fire accidents. These accidents first started as single event then they can spread leading to a domino accident. Fire domino accident have a great impact on a petroleum plant causing the loss of properties and fatalities. The common type of fire accidents that occur in the industry is pool fire. Fire domino can be categorized into three parts: primary event, escalation and secondary scenarios.